THE ROLE OF TRANSFORMATIONAL LEADERSHIP, COMPENSATION, AND MOTIVATION IN JOB SATISFACTION OF GENERATION Z IN WEST JAKARTA - Turangan, Joyce A.; Wijaya, Andi; Ruslim, Herman (Graduate Program of Universitas Tarumanagara, 2025)
Generation Z, known for its attachment to digital technology and preference for flexibility, possesses unique characteristics that influence their job satisfaction. This study aims to analyze the effects of transformational leadership, compensation, and motivation on the job satisfaction of Generation Z in West Jakarta. The study uses a quantitative method with a survey of 100 respondents selected through probability sampling with a simple random approach. Data were collected via questionnaires and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results indicate that compensation and motivation have a positive and significant effect on job satisfaction, whereas transformational leadership shows a positive but not significant effect. This study addresses the differing role of transformational leadership in enhancing job satisfaction among Generation Z compared to previous generations, suggesting that this leadership approach may be less effective for today's younger generation. This research provides valuable insights for companies in designing more effective management strategies to improve job satisfaction, retention, and productivity of Generation Z employees, particularly through compensation policies and motivation that align with their needs.